Un viaje ancestral : mujeres afrocolombianas, indígenas y campesinas del Valle de Aburrá en diálogo de saberes intercultural (2018)
ABSTRACT: The present article aims to reflect and make visible the political role that women have played as guardians, custodians and transmitters of the ancestral cultures of indigenous peoples, African-Colombians and peasants. Likewise, recognize the resistance and re-existence of some organizational experiences of diverse women in Medellin who struggle from their autonomy to maintain their identity, practices and knowledge in a context of a hegemonic and excluding city. With the purpose to transform the realities that affect them and subvert the political, social, economic and cultural model that as African, indigenous and peasant women denies, invisibilizes and locates them in a place of subordination. The importance of this work lies in giving the rightful place and legitimacy to ancestral knowledge, and in this sense, positioning women as a fundamental subject in the political and cultural struggles that arise from particular processes of struggle and emerge as intercultural and decolonial proposals that contribute to combat the Western capitalist model “of death”.